2008
DOI: 10.1300/j083v50n3_04
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of English Acculturation Stress and Its Relationships with Psychological and Physical Health Status in a Sample of Elderly Russian Immigrants

Abstract: This study aims to evaluate the factor structure and criterion validity of the English Language Acculturation Stress (ELAS) scale in a community-based sample of elderly Russian immigrants. The sample consists of 300 Russian immigrants with an equal number of females and males, from 59 to 93 years of age (Mean = 73.26, SD = 7.271). The majority of the respondents were married (72%) at the time the interviews were conducted. On average, the respondents have lived in the U.S. for about 7 years (SD = 3.00). We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Isolation, meaning to be separate from others [ 67 ], was linked to English language proficiency. Tran et al [ 68 ], found that isolation combined with a lack of English language skills resulted in older adult immigrants from the FSU being unable to complete tasks or participate in “social activities” [ 68 ]. Furthermore, Serafica [ 69 ], identified isolation as contributing to emotional distress among older adult Filipino immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…Isolation, meaning to be separate from others [ 67 ], was linked to English language proficiency. Tran et al [ 68 ], found that isolation combined with a lack of English language skills resulted in older adult immigrants from the FSU being unable to complete tasks or participate in “social activities” [ 68 ]. Furthermore, Serafica [ 69 ], identified isolation as contributing to emotional distress among older adult Filipino immigrants.…”
Section: Resultsmentioning
confidence: 99%
“…People who have less social support experience more acculturative stress than those who have more (Thomas & Choi, 2006). Social support can reduce the level of acculturative stress (Keel & Drew, 2004;Oh & Sales, 2002;Smart & Smart, 1995;Tartakovsky, 2007;Thomas & Choi, 2006;Tran & Huynh-Hohnbaum, 2008;Ye, 2006). Social support, especially emotional support, reduces acculturative stress in two aspects.…”
Section: Acculturative Stress and Social Supportmentioning
confidence: 99%
“…It may occur very slowly, particularly for those who immigrate during midlife or older age (Stevens, 1999). Lower acculturation is associated with depressed mood in FSU immigrants (Miller et al, 2006), but findings vary across other ethnic groups (Koneru et al, 2007; Tran et al, 2008). Immigration challenges may occur in all life domains, including difficulty finding work and managing routine activities such as transportation or shopping (Vinokurov, Birman, & Trickett, 2000).…”
Section: Cultural Factors and Depression In Immigrantsmentioning
confidence: 99%
“…The acculturative process can complicate developmental, family, and social dynamics, with significant repercussions and implications. One frequently monitored indicator of problematic adaptation in the post‐immigration period is depressed mood, potentially a precursor to clinical or major depression (Koneru, Weisman de Mamani, Flynn, & Betancourt, 2007; Tran, Sung, & Huynh‐Hohnbaum, 2008). Depression can have serious and debilitating consequences that include functional impairment and disability (Chapman & Perry, 2008).…”
mentioning
confidence: 99%